Mitochondrial small ribosomal RNA is present on polar granules in early cleavage embryos of Drosophila melanogaster. - Kashikawa, M.; Amikura, R.; Nakamura, A.; Kobayashi, S. (Development, Growth and Differentiation, 1999)
In Drosophila, formation of the germline progenitors, the pole cells, is induced by polar plasm localized in the posterior pole region of early embryos. The polar plasm contains polar granules, which act as a repository for the factors required for pole cell formation. It has been postulated that the factors are stored as mRNA and are later translated on polysomes attached to the surface of polar granules. Here, the identification of mitochondrial small ribosomal RNA (mtsrRNA) as a new component of polar granules is described. The mtsrRNA was enriched in the polar plasm of the embryos immediately after oviposition and remained in the polar plasm throughout the cleavage stage until pole cell formation. In situ hybridization at an ultrastructural level revealed that mtsrRNA was enriched on the surface of polar granules in cleavage embryos. Furthermore, the localization of mtsrRNA in the polar plasm depended on the normal function of oskar, vasa and tudor genes, which are all required for pole cell formation. The temporal and spatial distribution of mtsrRNA is essentially identical to that of mitochondrial large ribosomal RNA (mtlrRNA), which has been shown to be required for pole cell formation. Taken together, it is speculated that mtsrRNA and mtlrRNA are part of the translation machinery localized to polar granules, which is essential for pole cell formation.